Aetiology of arthritis in hospitalised children: an observational study. Issue 8 (2nd March 2015) - Aupiais, Camille; Ilharreborde, Brice; Doit, Catherine; Blachier, Audrey; Desmarest, Marie; Job-Deslandre, Chantal; Mazda, Keyvan; Faye, Albert; Bonacorsi, Stéphane; Alberti, Corinne; Lorrot, Mathie
Abstract : Background and objective: Arthritis in children has many causes and includes septic and viral arthritis, reactive arthritis and juvenile idiopathic arthritis (JIA). We aimed to describe the different types of arthritis among children hospitalised for a first episode of arthritis. Design: Retrospective, descriptive case series study. Setting: A French tertiary care centre. Patients: Children under 16 years of age hospitalised for an arthritis episode between 1 January 2008 and 31 December 2009. Main outcome measures: Demographic and clinical features were compared with χ 2 or Fisher's exact tests and non-parametric tests. Results: 173 children were hospitalised for a first episode of arthritis during the study period, with a male/female ratio of 1.14. The most frequent cause of hospitalisation was septic arthritis (43.4% of cases, 69.3% of which were due to Kingella kingae and 10.7% to Staphylococcus aureus ). JIA was responsible for 8.1% of cases and arthritis without any definitive diagnosis for 40.4%. Median age at diagnosis was 2.7 years (IQR 0.3–14.6) and was lower in the septic arthritis group (1.5 years; 1.1–3.4) than in the JIA group (4.7 years; 2.5–10.9) (p<0.01). Septic arthritis involved a single joint in 97.3% of cases, while JIA involved four joints in 14.3% of cases and two to four joints in 28.6% of cases (p<0.01). Conclusions: Septic arthritis was the most frequent cause of arthritis in hospitalised children. Despite the increasing application of microbiological molecular methods to synovial fluid analysis, further measures are required to improve the diagnosis of arthritis of unknown cause.